The Contribution of Hemoglobin Levels to Students’ Physical Fitness (Department of Physical Education, Sport, Health and Recreation, 2019)
This study was based on the low students’ physical fitness. This is due to various factors, one of which is the level of hemoglobin (Hb) in the blood. This study aims to determine the contribution of hemoglobin levels to students’ physical fitness. This research is classified into the type of quantitative research using a correlational research design that aims to investigate how far the relationship of variables obtained relates to other variables based on the magnitude of correlation coefficient. This study will see the relationship between hemoglobin levels as an independent variable (X) with physical fitness as the dependent variable (Y). The samples of this study were 56 active students. The instrument used to measure Hemoglobin levels is the sahli method, and to measure physical fitness is used Multi Stage Fitness Test (MSFT). The results of this study indicate that hemoglobin (Hb) levels have a significant relationship with students’physical fitness, where hemoglobin levels contribute 9.72% to students’ physical fitness.